2021
DOI: 10.1097/md.0000000000028091
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different handrail types and seat heights on kinematics and plantar pressure during STS in healthy young adults

Abstract: Handrail type and seat height both significantly influence sit-to-stand (STS) movement. However, research on the associations between handrail type, seat height, and their cumulative effect on STS kinematics and changes in plantar pressure distribution during STS under different handrail types and seat heights is insufficient. The main objective of this study was to investigate the effect of different handrail types and seat heights on the kinematics and plantar pressure in healthy adults during STS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…These papers used handrails at a fixed height and took the effect of grip position and trunk-tilt angle into account. Xiaolong Han and Xue [14] is the only study that has measured the effect of two grip positions and trunk-tilt angles at the seat-off point and found that the minimum knee torque occurred with a trunk-tilt angle of 30 degrees and grip positioned above the greater trochanter beneath the chest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These papers used handrails at a fixed height and took the effect of grip position and trunk-tilt angle into account. Xiaolong Han and Xue [14] is the only study that has measured the effect of two grip positions and trunk-tilt angles at the seat-off point and found that the minimum knee torque occurred with a trunk-tilt angle of 30 degrees and grip positioned above the greater trochanter beneath the chest.…”
Section: Discussionmentioning
confidence: 99%
“…The seat-off point is the critical point of transition when maintaining posture is most difficult and a large load is being tolerated by the lower limbs [11]. Studies have analysed the functionality of lower limbs during the STS transition and identified the peak torques required in the lower limb joint at the seat-off point [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Step one: Train volunteers in the motion of standing up to ensure that the subjects stand up in a natural motion, eliminating interference from other factors [27]. A uniform sitting posture with a starting knee angle of 90 degrees is specified, and the thighs must remain horizontal, as shown in Figure 8.…”
Section: Experimental Stepsmentioning
confidence: 99%